Acute‐on‐chronic liver failure: Excellent outcomes after liver transplantation but high mortality on the wait list. Issue 8 (25th July 2013) - Finkenstedt, Armin; Nachbaur, Karin; Zoller, Heinz; Joannidis, Michael; Pratschke, Johann; Graziadei, Ivo W.; Vogel, Wolfgang
<x xml:space="preserve">Abstract</x> Acute‐on‐chronic liver failure (ACLF) is characterized by high short‐term mortality. Liver transplantation (LT) is a potential therapy for patients who do not improve with supportive measures, but the efficacy of LT has not been shown. The aim of this study was to investigate the feasibility of LT and to determine the postoperative outcomes of patients with ACLF. All patients referred to our liver unit between 2002 and 2010 were registered in a database. The diagnosis of ACLF was made in accordance with the Asian Pacific Association for the Study of the Liver consensus. The post‐LT outcomes were compared with the outcomes of a cohort of patients with chronic liver disease who underwent transplantation for other indications during the same period. One hundred forty four of 238 patients fulfilled the ACLF criteria. In an intention‐to‐treat analysis, the median transplant‐free survival time was 48 days. Multiorgan failure was the most common cause of death. Ninety‐four patients (65%) were evaluated for LT, 71 patients (49%) were listed, and 33 patients (23%) finally underwent deceased donor LT; this resulted in a wait‐list mortality rate of 54%. Patients who developed infectious complications (particularly pneumonia and/or sepsis) and patients who received renal replacement therapy or mechanical ventilation were less likely to undergo LT. The 1‐ and 5‐year survival rates of 87% and 82% were comparable to the rates for non‐ACLF patients. In conclusion, this study shows that LT remains the only therapeutic option for the vast majority of patients with ACLF. However, LT was feasible in less than one fourth of the patients with a 5‐year survival rate greater than 80%. Liver Transpl 19:879‐886, 2013. © 2013 AASLD.